PENGARUH KOMPOSISI MEDIA TANAM YANG BERBEDA DAN PEMBERIAN AIR LERI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L.) PADA SISTEM VERTIKULTUR DI LAHAN KERING - Ndona, Priscilia Jeani (Universitas Islam Madura, 2023)
This study aims to determine the interaction effect of the composition of the planting medium and the application of leri water on the growth and yield of lettuce (Lactucasavita L.) verticulture system in dry land. To determine the effect of planting media composition on the growth and yield of lettuce (Lactucasavita L.) verticulture system on dry land. To determine the effect of leri water application on the growth and yield of lettuce (Lactucasavita L.) verticulture system in dry land. This study used a split plot design (RPT) with 2 factors consisting of a main plot and subplots. The main plot was the planting medium, (M) which consisted of: soil : biochar (1:1) (M1), soil : guano (1:1) (M2), soil : biochar: guano (1:1:1) ( M3) and subplots were leri water, (A) consisting of 20 mL/L (A1), 60 mL/L (A2), 100 mL/L (A3). An interaction occurred in the observation of total plant fresh weight and shoot fresh weight with the best treatment being the composition of the planting medium soil: biochar: guano (1:1:1) with the addition of 60 mL/L of water. The composition of the growing media affected the observation of plant height 7-28 DAP, number of leaves 7 and 14 DAP, total plant fresh weight, shoot fresh weight, root fresh weight and root length with the best treatment being the composition of the single planting medium soil:biochar:guano ( 1:1:1). Giving leri water had a significant effect on the number of leaves observed at 14 and 28 DAP, total fresh weight of plants and fresh weight of shoots with the best treatment in giving leri water 60 mL/L of water.